Inhibition of PNCK inflames tumor microenvironment and sensitizes head and neck squamous cell carcinoma to immune checkpoint inhibitors - Ying Li; Jianmin Wang; Tingting Lin; Qin Ding; Youliang Weng; Wanzun Lin; Xiaosan Lin; Hanxuan Yang; Wenqian Xu; Hongmei Ying; Sufang Qiu (Journal for ImmunoTherapy of Cancer)
Background The landscape of the tumor microenvironment (TME) is intricately linked to the development of head and neck squamous cell carcinoma (HNSCC) and significantly influences immunotherapy efficacy. Recent research has underscored the pivotal role of PNCK in cancer progression, yet its relationship with immunotherapy remains elusive.Methods We leveraged sequencing data from our cohort and public databases to evaluate PNCK expression, prognostic significance, and immune efficacy prediction. In vitro and in vivo experiments explored the role of PNCK in HNSCC progression. Animal models assessed the therapeutic effects and survival benefits of PNCK knockdown combined with immune checkpoint inhibitors (ICIs). Single-cell transcriptomics analyzed the impact of PNCK on the TME, and proteomic studies elucidated the mechanisms.Results PNCK exerts multifaceted critical roles in the progression of HNSCC. Lower PNCK expression is associated with improved prognosis, enhanced immune cell infiltration, and increased responsiveness to ICIs. Conversely, PNCK promotes HNSCC cell migration, invasion, proliferation, colony formation, zebrafish angiogenesis, and tumor growth in mice. Moreover, targeting PNCK enhances sensitivity to ICIs and leads to significant alterations in the T-cell and B-cell ratios within the TME. These changes are attributed to the inhibition of nuclear transcription of PNCK-phosphorylated ZEB1, which restricts cytokine release and inflames the immune microenvironment to regulate the TME.Conclusions Inhibition of PNCK may be a potential strategy for treating HNSCC, as it may activate the immune response and improve the TME, thereby enhancing the efficacy of immunotherapy for HNSCC patients.